A new automatic GEP-Cluster algorithm. (2015) - Du, Xin; Ni, Youcong; Ye, Peng; Xiao, Ruliang
GEP-Cluster, a clustering algorithm based on Gene Expression Programming (GEP), is a kind of automatic cluster algorithm for the clustering problem with unknown clustering number. However, its performance, especially the step for computing the distance between the data object and the corresponding cluster centre, can be improved. Parallel is undoubtedly a good method for improving the performance of algorithm. This paper proposes an improved auto-clustering algorithm based on Compute Unified Device Architecture (CUDA) and GEP, called ICGEP-Cluster. Experimental results show that ICGEP-Clustering has a better performance than GEP-Cluster, especially for the large scale of data objects.